â€œWatching English Movie Helps Me!â€: Language Exposure and Metacognitive Awareness on TOEFL - Fata, Ika Apriani; Mutia, Nyak (Lingua Cultura, 2017)
This research was conducted to investigate the correlation between metacognitive and language exposure to TOEFL of reading section. The framework of metacognitive was promoted by Veenman et al. and the model of language exposure was promoted by Magno et al. (2009). This research implemented a descriptive qualitative study. The questionnaire and rubricof metacognitive were applied as research instruments respectively. Furthermore, ten freshmen at Syiah Kuala University from various majors considered as strategic readers whose TOEFL score ranges of 400 above. It is prominently revealed that language exposures have a contribution for strategic readers in answering TOEFL in the reading section, in particular,media exposure. The respondents have a tendency to seek out the media availability as the major side on mastering reading TOEFL meanwhile language exposure at home is the lowest impact on students. In addition, metacognitive awareness has an impact on studentsâ€™ performance in answering reading test of TOEFL the metacognition implementation, the students are eventually categorized on knowledge regulation in which the students relate the knowledge of TOEFL into planning, implementing strategies or information management, monitoring, correcting/debugging, and evaluating comprehension. It is assumed that this study has weakness on informants taken therefore as further studies, the researcher trigger to probe students of 500 TOEFL score above to investigate their learning strategy and language exposures accordingly.